2021
DOI: 10.33265/polar.v40.5498
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of social behaviour among immature belugas (Delphinapterus leucas) in managed care

Abstract: Belugas (Delphinapterus leucas) in managed care have been reported to show seasonal variation in socio-sexual behaviour, hormone levels and respiration rates; however, little is known about the social interactions of wild belugas when they are not in summer, near-shore congregations. To better understand if belugas show seasonal variation in social interactions, this study recorded the behaviour of 10 belugas (five females, five males, ranging from birth to 10 years of age) housed in managed care. Social inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Social behavior, including sexual behavior, has been shown to vary depending on the time of the year in odontocetes (Glabicky et al, 2010; Ham et al, 2021b; Samuels & Gifford, 1997) as well as in other animals (e.g., Buck & Barnes, 2003), which could result in different scarring rates. The density of fresh tooth rake marks was higher during the wet season (May–October) than during the dry season (November–April).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social behavior, including sexual behavior, has been shown to vary depending on the time of the year in odontocetes (Glabicky et al, 2010; Ham et al, 2021b; Samuels & Gifford, 1997) as well as in other animals (e.g., Buck & Barnes, 2003), which could result in different scarring rates. The density of fresh tooth rake marks was higher during the wet season (May–October) than during the dry season (November–April).…”
Section: Discussionmentioning
confidence: 99%
“…The calves' high density of rake marks and low density of notches could therefore be explained by frequent play and socio‐sexual interactions, and infrequent or low‐intensity agonistic interactions. As they grow older, juvenile odontocetes may start to engage in more agonistic and socio‐sexual interactions in addition to playful interactions (Ham et al, 2021b; Lee et al, 2019), and with increased intensity and strength, inflicted rakes and bites may be more severe, resulting in notches on the dorsal fin. High tooth rake density among mid‐aged females may be the result of frequent interactions with male dolphins (Krzyszczyk et al, 2017), maybe before juvenile males leave the maternal group.…”
Section: Discussionmentioning
confidence: 99%
“…As this review shows, belugas in aquariums exhibit many behaviours that match those observed in their wild counterparts. It is also clear that, because of the greater opportunities for sustained observations, investigations conducted in zoological institutions can help Chernetsky et al 2011;Krasnova et al 2012;Alekseeva et al 2013;Krasnova et al 2014;O'Corry-Crowe et al 2020 Clear male-male associations during most of the year, in both adult and immature belugas Far fewer close associations in females Seasonal effects Mazikowski et al 2018;Ham et al 2021 Functional role for male-male associations?…”
Section: Discussionmentioning
confidence: 99%
“…One criterion described by Smith (1997) that could not be verified for belugas was if there are facial and/or vocal expressions made by the animals during the play fighting encounter as neither of these were observable in the data collection method (i.e., no hydrophone present, facial expressions not visible). Most occurrences of MtMIs occurred without play behaviors preceding or following them (Ham, 2021), though, other play behaviors (e.g., sexual play, object play) occurred at other points in a given observation.…”
Section: Methodsmentioning
confidence: 99%
“…The seasonal trend in MtMIs, with both males and females peaking in summer months, found in the present paper, supports the possibility of this behavior having a sociosexual or courtship component. Not only does mating (Doan & Douglas, 1953;Heide-Jørgensen & Teilmann, 1994;Krasnova et al, 2009;Robeck et al, 2005;Shelden et al, 2020) and calving vary seasonally (Sergeant, 1973), peaking in the summer months, so does sociosexual behavior and other affiliative behavior (Ham, Lilley, Miller, & Hill, 2021). This heightened social arousal during the summer months could also account for the seasonal trend of MtMIs.…”
Section: Are Mtmis Used To Facilitate Social Relationships?mentioning
confidence: 99%